Social networking and mobile phone usage of East African students in Malaysia. (1st June 2018) - Wanda, Judith Flora Etabale; Nair, Govindan Velaithan; Periayya, Thinavan; Wilson, Sharon
With the current development in technology, mobile phones have become progressively more popular as they are one of the frequently used means of communication that people rely on because of their features. While people find mobile phones convenient and useful, international students in foreign countries tend to appreciate them more and are more dependent on them in order to maintain their social networks. The literature states that students from East Africa carry along their own culture with them, making it difficult for them to accept and adapt to the new culture easily. This includes meeting face to face in small areas and groups where friendships are formed through frequent interaction. Based on a survey conducted in various private universities in the Klang Valley where foreign students of East African origin are studying, students' mobile phone use for social networking was examined. The results showed that there was a positive significant relationship between variables such as interaction, interpersonal communication and social networking for maintenance of social network; however, there was no significant difference in mobile phone dependency for social networking among university students of East African origin and the duration of stay in Malaysia. Although they may be unable to interact in person, social networking proved useful to strengthen relationships that already exist and enhanced the feelings of closeness to others. As technology has advanced, there have been adjustments in the users' attitudes towards particular technologies, hence this has generated new social and cultural phenomena. This phenomenon has in a way changed the way mobile phones evolve as they represent social construction of technology. This social construction of the mobile phone is seen in the symbiotic relationship between the users of the technology. Users such as these students respond to the advancement of technologies such as mobile phones, which in turn has seen them develop social and cultural changes.